1998
DOI: 10.1128/jvi.72.9.7664-7668.1998
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Lymphotropic Virus Type 2 (HTLV-2) Provirus in Circulating Cells of the Monocyte/Macrophage Lineage in Patients Dually Infected with Human Immunodeficiency Virus Type 1 and HTLV-2 and Having Predominantly Sensory Polyneuropathy

Abstract: We investigated the presence of human T-lymphotropic virus type 2 (HTLV-2) DNA in the peripheral blood mononuclear cell subsets obtained from 18 patients coinfected with human immunodeficiency virus type 1 and HTLV-2, 6 of whom also had predominantly sensory polyneuropathy (PSP). HTLV-2 DNA and RNA were found in CD8- and CD19-positive cells, and, for patients with PSP, in CD14-positive cells as well. Furthermore, the patients with PSP had higher proviral loads than those without PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In contrast with HTLV‐I, the role of HTLV‐II in neurological disease remains poorly understood. However, there is increasing evidence that the infection may be associated with several different neurological disorders in some individuals 2, 51–69. To date, some 15 to 20 cases of possible HTLV‐II–associated neurological syndromes have been published.…”
Section: Neurological Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with HTLV‐I, the role of HTLV‐II in neurological disease remains poorly understood. However, there is increasing evidence that the infection may be associated with several different neurological disorders in some individuals 2, 51–69. To date, some 15 to 20 cases of possible HTLV‐II–associated neurological syndromes have been published.…”
Section: Neurological Diseasementioning
confidence: 99%
“…In a recent study of a cohort of HIV‐1 coinfected individuals, the prevalence of antibodies to HTLV‐II infection was found to be significantly higher in those with a predominantly sensory polyneuropathy (PSP) compared with asymptomatic controls 64. In addition, patients with PSP were found to have higher proviral loads than those without PSP 65. However, further studies are required to confirm an association with HTLV‐II infection and the development of such neuropathies.…”
Section: Neurological Diseasementioning
confidence: 99%
“…The nucleic acids were then extracted by means of centrifugation through a glass fiber fleece, and eluted using 50 l of nuclease-free sterile bidistilled water. The RNA-containing samples were finally digested with DNAse I. HTLV-2 proviral DNA and RNA levels were, respectively, determined by means of nested-PCR and nested-RT-PCR using primers amplifying a sequence included in the tax gene (sense outer primer position at nucleotides 7219-7238, antisense position 7483-7464; sense inner primer position 7248-7267; antisense position 7406-7386) as described elsewhere (Zehender et al, 1998). The same primers were also used to detect HTLV-1 tax sequences (amplified region 7358-7516).…”
Section: Htlv Nucleic Acid Detection and Semiquantitationmentioning
confidence: 99%
“…HTLV-2 has cell tropism for T cells, in particular CD8-positive cells. We have recently shown that HTLV-2 infects cells of the monocyte/macrophage lineage in patients with PSP and B lymphocytes (Zehender et al, 1998). The mechanisms by which HTLV-2 may damage the nervous system and induce cell transformation are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…America, the seroprevalence of the virus ranges from 0.4% to 24% among various injection-drug-using populations [2] and approaches 0.03% among blood donors [3], with an estimated 140,000 infected persons in the United States [1]. The cellular tropism of HTLV-II was initially reported to be toward CD8 + T lymphocytes; however, subsequent studies have demonstrated that CD4 + T lymphocytes, B lymphocytes, and monocytes can carry the proviral genome in infected persons [4,5]. Thus, HTLV-II-related immune defects may extend to multiple components of the immune system, each of which may contribute to diminished protection against infectious diseases if functionally impaired.…”
mentioning
confidence: 99%